Volume, Volatility, and the Dispersion of Beliefs - Shalen, Catherine T. (Review of Financial Studies, 1993)
I examine a two-period noisy rational expectations model of a futures market and show that the dispersion of expectations about a weighted average of future prices measures both the additional volatility and the additional expected.volume of trade associated with noisy information. The role played by dispersion helps clarify several stylized facts concerning volume and price behavior. Specifically, dispersion can be a factor contributing to the positive correlation between volume and absolute price changes, and the positive correlation between consecutive absolute price changes. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.